David as a Prophet in the Text of "David’s Compositions" (11Q5 xxvii 2–11) against the Background of the Qumran Literature - Biegas, Marcin (The Biblical Annals, 2025)
The main aim of this paper is to analyse the biblical figure of King David as a prophet based on the apocryphal text of “David’s Compositions,”which is part of the Great Psalms Scroll from Cave 11 at Qumran (11Q5 xxvii 2–11). The paper consists of three parts. The first part is an analysis of the text of“David’s Compositions” itself. It includes the Hebrew text with its translation into English, the context, and the detailed exegesis of the composition with a strong emphasis on the interpretation of the ending of v. l.3 and the first half of vv. l.4 and l.11 (col. xxvii), relevant to the subject of the presentation. The objective of the second part is to look, in the context of David’s Compositions,” at the terminology defining the function and figure of the prophet in the Qumran Caves Scrolls. This enables us to limit a huge number of manuscripts only to those in which this terminology occurs. Their content is further verified in terms of their connection to the figure of David. The final, third part concerns the interpretation of three fragments from 4QMMT.